Production, Purification and characterization of bioactive compounds from locally Streptomycesrochei M78 - Hayder , Nadhim H.; Mahmood, Marwa S. (Iraqi Journal of Science, 2022)
The aim of the current study was to optimize different cultural and environmental conditions for production the antibacterial bioactive metabolites by Streptomyces rochei M78 isolated from agriculture soil, in Baghdad, Iraq. The effect of various parameters such as, culture media, incubation time, pH, carbon and nitrogen sources, C: N ratios and inducers on antibacterial metabolite production was studied by varying single parameter at a time. It was found from the results that higher metabolite production by isolate observed using starch casein broth (SCB) as the best production medium, at initial pH 7.0.Starch andcasein +yeast extract + peptone appeared to be the best carbon and nitrogen sources respectively and C: N ratio of 4: 1 after 72 h of incubation for optimal production of antibacterial metabolites.Optimization studies indicated that antibacterial metabolites production was associated with bacterial growth, and that the presence of inducers, such asedible oils and diesel oil as well as amino acids in the medium also enhanced antibacterial metabolites production.The most bioactive compounds were produced with soybean oil as the sole carbon source, and leucine as amino acid, yielding an inhibition zone more than 35 mm against all tested pathogenic bacteria.Among different solvents used for the extraction of antibacterial metabolite, ethyl acetate was found to be the best for solvent extraction of the metabolites yielding 2.18 g /l of red to brown extract with oily nature. The antibacterial activity of different extraction fractions of the metabolites showed that the ethyl acetate extract was the most active agent against tested pathogenic bacteria.Physiochemical characteristic of antimicrobial metabolites revealed that the antimicrobial metabolite was red to brown in color, having gummy and oily nature. The purified metabolite was soluble in different solvents, with a melting point of 150 °C. The metabolites of isolate M78 were stable at pH that varies from 4 – 11, maximum antibacterial activity was found at pH 7 and at temperatures ranging from 25 to 100 °C, maximum at 25 °C. Higher bactericidal concentration (BC) of the compound against Gram positive and Gram negative bacteria was determined as 250 μg/ml. The results showed that MBC values of the active metabolite had an impact at lower concentrations than those of standard antibiotic against tested pathogenic bacteria, suggesting that the metabolite was more effective.Theminimum inhibitory concentration value of compounds was 500 μg/ml against all tested bacterial isolates. Thin layer chromatography analysis of active metabolites showed two spots having an Rf value = 0.72 and 0.80.The FTIR spectrum of antibacterial compounds exhibited the presence of OH, C=O functional ester group, and C-H and CH3 groups in the structure. GC-MS analysis of active metabolites detected a total of 23 peaks; two major hydroxylated fatty acids were then identified as octadecanoic acid, 2-(2-hydroxy ethoxy) ethyl ester and tridecanoic acid, 3 methyl-, methyl ester with relative abundance of 100 and 33.63 % respectively.